Greater sage‐grouse response to bentonite mining. Issue 4 (27th February 2019) - Pratt, Aaron C.; Beck, Jeffrey L.
ABSTRACT: The greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse) has undergone range contraction and population decline because of anthropogenic land surface disturbances; yet, there is little information on the effects of mining on sage‐grouse populations. In the Bighorn Basin of Montana and Wyoming, USA, bentonite mining is a growing source of surface disturbance that contributes to loss of sagebrush ( Artemisia spp.) habitat. We evaluated the response of sage‐grouse to active and reclaimed bentonite mining, relative to nesting, brood‐rearing, adult breeding, and adult winter habitat, through resource selection and habitat‐specific mortality risk analyses, based on female sage‐grouse ( n = 321) monitored with telemetry from 2011–2015. A greater proportion of our monitored sample was exposed to mining disturbance during winter (65%) than during other seasons (range = 25%–34%). We observed avoidance of all mining disturbance for selection of nesting habitat ( n = 378 nests), adult breeding habitat ( n = 1, 978 locations), and adult winter habitat ( n = 1, 365 locations). Evidence was inconclusive for avoidance of mining for brood‐rearing habitat ( n = 754 locations). We also observed increased adult breeding season mortality risk ( n = 62 mortality events; n = 285 female sage‐grouse) associated with active mining disturbance but observed no effect on nest success ( n = 207 mortality events; n = 378 nests). Evidence was inconclusive for increased mortality risk associated with broods ( n = 48 mortality events; n = 157 broods) and adults during winter ( n = 31 mortality events; n = 220 female sage‐grouse). Stakeholders in the Bighorn Basin should be flexible and proactive to minimize the negative effects of bentonite mining on sage‐grouse habitat use and demographic rates. Stakeholders should prioritize the conservation of winter habitats because of the influence on a greater proportion of the population and because of the lower regulatory priority given to winter habitat and they should strive to perfect mining reclamation to return disturbed sites back to pre‐disturbance conditions to minimize long‐term effects of the mines on sage‐grouse. © 2019 The Wildlife Society. Abstract : We documented greater sage‐grouse avoidance of, and reduced demographic rates associated with, bentonite mining disturbance. Sage‐grouse conservation stakeholders should be flexible and proactive to minimize the negative effects of mining.